Iron Machine Sales Data Processing At Pt. Multiuser-Based Panca Teknik Banjarmasin - Distan Madani (Institute of Computer Science (IOCS), 2021)
In processing sales and production data at PT. Panca Teknik Banjarmasin, is an important activity. The distributed data processing is still using Microsoft Excel and Microsoft Word. Therefore, to facilitate employees in data entry, ordering goods and selling goods, the authors seek to use a computerized system in processing the data. Data collection and analysis were carried out in an effort to solve these problems. The research method used in making this system, starting from data collection, problem analysis, system design to system creation is the observation method, direct interviews with employees of PT. Five Techniques. By using this system, the distribution of sales and production data processing at PT.